2012
DOI: 10.1016/j.jvs.2011.09.093
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistula after endovenous ablation for varicose veins

Abstract: Endovenous ablation, using radiofrequency or laser, is becoming the mainstay of treatment for symptomatic varicose veins in the setting of saphenous vein incompetency. Both procedures have been shown to produce high rates of truncal vein occlusion with few complications. This article presents three patients who developed arteriovenous fistula (AVF) following great saphenous vein treatment: two following radiofrequency ablation (RFA) and one following laser ablation. This is the first published report of AVF fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…More invasive imaging exams and surgical or endovascular treatment should be reserved for patients who become symptomatic. 8 In the case described here -an asymptomatic patient whose AVF was found during a routine sonographic follow-up examination -it is believed that the cause of AVF formation was probably linked to a iatrogenic injury during the perivenous tumescence procedure. Initially, two attempts were made at compression with a linear transducer, separated by a 1-week interval, but they were unsuccessful, probably because of the high throughput of the AVF.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…More invasive imaging exams and surgical or endovascular treatment should be reserved for patients who become symptomatic. 8 In the case described here -an asymptomatic patient whose AVF was found during a routine sonographic follow-up examination -it is believed that the cause of AVF formation was probably linked to a iatrogenic injury during the perivenous tumescence procedure. Initially, two attempts were made at compression with a linear transducer, separated by a 1-week interval, but they were unsuccessful, probably because of the high throughput of the AVF.…”
Section: Discussionmentioning
confidence: 79%
“…These patients were initially managed conservatively and two of them enjoyed spontaneous resolution in 12 weeks, while the third's fistula remained patent, but its peak systolic velocity reduced over 18-months of follow-up. 7 In a review published in 2011, Rudarakanchana et al 8 reported 11 cases described in the literature of AVF after venous thermal ablation, the majority after EVLT. The symptoms displayed by patients after formation of the AVF varied greatly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Most describe small fistulas involving either the greater or lesser saphenous veins. To our knowledge, there is only one other reported case of fistulation occurring within the iliac system.…”
Section: Discussionmentioning
confidence: 99%
“…AVFs can lead to partial patency of ablated segments with pulsatile flow on duplex ultrasound. AVFs between the proximal SSV and the sural artery or between the superficial external epigastric artery and proximal GSV have been described (44,45).…”
Section: Duplex Ultrasound After Treatmentmentioning
confidence: 99%